Pengaruh Konformitas Hedonis, Pengendalian Diri, dan Literasi Keuangan terhadap Perilaku Konsumtif Mahasiswa - Silvia, Ita; Purnama, Dian Normalitasari (Universitas Galuh, 2024)
Consumptive behavior is the habit of consuming products in the form of goods and services that are not based on the needs and uses of the product but based on desires and desires that are not carefully considered. This study aims to find out: (1) The influence of hedonic conformity on student consumptive behavior; (2) The effect of self-control on student consumptive behavior; (3) The effect of financial literacy on student consumptive behavior. This research is a correlational research with quantitative methods. The instruments used were questionnaires and were analyzed by descriptive statistical analysis, prerequisite tests, and hypothesis tests. The results showed a significant positive influence of hedonic conformity on the consumptive behavior of students, there was a significant positive influence of self-control on the consumptive behavior of students, and there was a significant negative influence of financial literacy on consumptive behavior. The R Square value of this study was 0.592 so that hedonic conformity, self-control, and financial literacy affected student consumptive behavior by 59.2% while the remaining 40.8% was influenced by other factors outside the study.